TERAPI KOMPLEMENTER KAYU MANIS PADA REMAJA DENGAN NYERI DISMENORE - Erawati Pasaribu; Mona, Silvia (Universitas Batam, 2026)
Primary dysmenorrhea is a global problem with a high prevalence, including in Indonesia. Risk factors include early age of menarche, nulliparity, family history, and a sedentary lifestyle. Cinnamon aromatherapy contains analgesic and antispasmodic compounds, proven effective in reducing menstrual pain through relaxation, anti-inflammatory effects, and stimulation of natural endorphins. This study aimed to determine the effect of cinnamon complementary therapy on adolescents with dysmenorrheal pain. The research method used a quasi-experimental approach with a one-group pretest-posttest without control. The study was conducted in August 2025 at the Kuala Kampar Community Health Center. The population of adolescents experiencing dysmenorrhea was 39 respondents. The sampling technique used total sampling, resulting in a sample size of 39. Data were analyzed using SPSS. The results showed that the average dysmenorrheal pain in adolescents before cinnamon complementary therapy was 3.90, while after therapy it decreased to 1.69. The statistical test results showed a significant difference with a p-value of 0.001 (p<0.05), thus concluding that cinnamon complementary therapy is effective in reducing dysmenorrhea pain in adolescents. Adolescents are encouraged to consider cinnamon as a safe complementary therapy to reduce dysmenorrhea, along with a healthy lifestyle through physical activity, stress management, and a balanced diet. Keywords: Dysmenorrhea, Pain, Cinnamon, Adolescents, Complementary Therapy